The Effect of Profit Margin, Asset Turnover, and Leverage on Sustainable Growth Rate in Consumer Goods Industry Companies Listed on the Indonesia Stock Exchange - Azhari Hidayat Fikri; Aspyan Noor; Zaki Fakhroni (INOVASI: Jurnal Ekonomi, Keuangan, dan Manajemen, 2025)
The Sustainable Growth Rate is the maximum sales growth that the company can achieve without changing its capital structure. Therefore, the sustainable growth rate is considered useful as it can describe the company's performance. This study aims to analyze the effect of profit margin, asset turnover, and leverage on sustainable growth rate in consumer goods industry companies listed on the Indonesia Stock Exchange. By using purposive sampling method, 18 companies were obtained as research samples with 2016-2020 used as the research period. The analytical method used is multiple linear regression analysis method. The results of the study show that: (1) profit margin has a positive and significant effect on the sustainable growth rate; (2) assets turnover has a positive effect on sustainable growth rate; (3) leverage has no significant positive effect on sustainable growth rate